Youth services and public libraries - Higgins, Susan E. (Assistant professor) (Chandos information professional series., 2007)
Youth Services and Public Libraries offers strategies to match the information needs and wants of children and young adults in public libraries and translates these into knowledge for providing relevant services. The latest trends in service provision are covered within the context of appropriate management, programming and marketing of services. The book is grounded in the principles of public library services to children and young adults everywhere. Links practical application of library programming to theoretical foundations of serviceIllustrates concepts with reference to the developmental needs of children and young adultsDescribes how to implement library policies which recommend, design, direct, supervise and evaluate active youth services programs.